Recursos educacionais abertos nas práticas didáticas dos professores de biologia - Somavilla, Giana (2020)
This study, linked to the Professional Master's Course in Networked Educational Technologies, in the UFSM Network Educational Technology Management Research Line - RS, analyzed whether or not changes occurred in the planning/elaboration of the teaching materials of the Science/Biology teachers who participated in the Course ―Small Open Online Course - REA - Education for the Future‖, Notice 02/2017 - Gaucho Researcher Program (PqG), which aimed to introduce and deepen the integration of hypermedia educational technologies, especially Open Educational Resources ( REA), to consolidate educational-methodological innovation in RS Basic Education. From this specific training context, it was sought to analyze the changes in actions of some cursors, instigating and analyzing the possibilities and challenges of using OER as teaching-learning resources. The research, of qualitative approach, had as procedure the case study and was structured in four stages. The first step was to follow the Course "Small Open Online Course - REA - Education for the Future" - 2019 Edition as a teacher / trainer. In the second stage, the identification and selection of participants took place and, as the first tool of data collection, the activities carried out during this Course were counted. As a third step, a questionnaire was applied for teachers and, from it, held the discussion of the collected data. As a fourth and final stage, the final product - the elaboration of an Open Educational Resource, in the form of educational material, as a grant to work on a content of the First Year of High School in the discipline of Biology, namely, on the differences between prokaryotes / eukaryotes cells, differences between animal / plant cells; plasma membrane - functions, structure, properties, specializations and transport of substances through the cell membrane. As a result, it could be observed that the participants of the survey already used these resources; but some, without being aware what an OER really is. After the analysis, it was noticed that the Course ―Small Open Online Course - REA - Education for the Future‖ generated changes of action in the teachers who participated in the research, who have come to know / differentiate RE from REA and integrate REA in the planning of their teaching practices, although they still feel shy about making these materials available on the network in an open way to assist other Science / Biology teachers. At the moment this happens in fact, will be expanding the possibilities of REA available in the network, providing better sharing of knowledge and teaching-learning quality.